A handbook of Malaysian cases: contemporary issues in marketing and management - Quoquab, Farzana (Partridge, 2016)
A Handbook of Malaysian Cases: Contemporary Issues in Marketing & Management” is the compilation of 11 Malaysian cases which provides significant insights to its readers about the problems and prospects faced by Malaysia based companies. These cases highlight the issues pertaining to Marketing, Human Resource Management, Business Ethics, Strategic Management, Entrepreneurship and Leadership.